2017
DOI: 10.1098/rsbl.2017.0240
|View full text |Cite
|
Sign up to set email alerts
|

Responses of neurogenesis and neuroplasticity related genes to elevated CO 2 levels in the brain of three teleost species

Abstract: The continuous increase of anthropogenic CO in the atmosphere resulting in ocean acidification has been reported to affect brain function in some fishes. During adulthood, cell proliferation is fundamental for fish brain growth and for it to adapt in response to external stimuli, such as environmental changes. Here we report the first expression study of genes regulating neurogenesis and neuroplasticity in brains of three-spined stickleback (), cinnamon anemonefish () and spiny damselfish () exposed to elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…The lack of regulation of DCX gene expression contrasts with previous data obtained in stickleback indicating up-regulation of this gene by OA, but is in line with responses observed in cinnamon anemonefish and spiny damselfish (Lai et al 2017a). Lai et al suggested that interspecies variability in the sensitivity of DCX gene expression to OA may reflect differential physiological plasticity between fish species (Lai et al 2017a). The absence of DCX gene regulation observed in the present study may not be related to a low molecular plasticity of European sea bass brain structure with respect to acidified condition.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The lack of regulation of DCX gene expression contrasts with previous data obtained in stickleback indicating up-regulation of this gene by OA, but is in line with responses observed in cinnamon anemonefish and spiny damselfish (Lai et al 2017a). Lai et al suggested that interspecies variability in the sensitivity of DCX gene expression to OA may reflect differential physiological plasticity between fish species (Lai et al 2017a). The absence of DCX gene regulation observed in the present study may not be related to a low molecular plasticity of European sea bass brain structure with respect to acidified condition.…”
Section: Discussionsupporting
confidence: 83%
“…The PCO2 levels associated to OA that we tested (i.e. ≈590 µatm for Control condition at PH total= 7.9; ≈980 µatm at pH7.7; ≈1520 µatm at pH7.5) were higher than those used in previous studies (Lai et al 2017a;Porteus et al 2018). However, the  PCO2 of ≈500 µatm and ≈1000 µatm that we have chosen to simulate OA were similar and based on IPCC RCP6.0 and RCP8.5 scenario (Collins 2014).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In vertebrates, GABA can act as a trophic factor (a molecule supporting cell survival) through the GABA A R, influencing cell proliferation, migration and differentiation (Owens and Kriegstein, 2002;Sernagor et al, 2010). In a fish, the three-spined stickleback Gasterosteus aculeatus, genes involved in neurogenesis and neuroplasticity were upregulated after exposure to ∼1,000 µatm pCO 2 compared to control (∼330 µatm pCO 2 ) (Lai et al, 2017). Similarly, GABA induces cellular differentiation and proliferation in abalone larvae (Morse et al, 1980).…”
Section: The Effects Of Altered Igaba Receptor Functioningmentioning
confidence: 99%
“…Further, fishes are becoming valuable models to study impacts of anthropogenic noise, pollution, and climate change on sensory and brain function (Ashur et al, 2017;Braun, 2015;Fisher and Oleksiak, 2007;Lai et al, 2017), with important consequences for management and conservation. Sensory cues play an integral role in the daily lives and survival of marine and freshwater organisms, including influences on homing, settlement, predator detection and evasion, foraging, conspecific social interactions, and reproductive interactions.…”
Section: Fish As Models In the Neurosciencesmentioning
confidence: 99%